60=2(4x-3)

Simple and best practice solution for 60=2(4x-3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 60=2(4x-3) equation:


Simplifying
60 = 2(4x + -3)

Reorder the terms:
60 = 2(-3 + 4x)
60 = (-3 * 2 + 4x * 2)
60 = (-6 + 8x)

Solving
60 = -6 + 8x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-8x' to each side of the equation.
60 + -8x = -6 + 8x + -8x

Combine like terms: 8x + -8x = 0
60 + -8x = -6 + 0
60 + -8x = -6

Add '-60' to each side of the equation.
60 + -60 + -8x = -6 + -60

Combine like terms: 60 + -60 = 0
0 + -8x = -6 + -60
-8x = -6 + -60

Combine like terms: -6 + -60 = -66
-8x = -66

Divide each side by '-8'.
x = 8.25

Simplifying
x = 8.25

See similar equations:

| -2(5-9v)=25+7v | | 802-2993*sin(x)-293*sin(2*x)=0 | | 2/x+3=-19/4 | | 6a+5-2(a-6)= | | 5-4[5-(8y-5)]= | | 2/3x+19/6 | | 1/4m-1/4+1/3m+1/6 | | 450u= | | 458y+11= | | x/3+2/5=2 | | 1/2+5=x | | 458y+13= | | 4(8y-3)-(9y+7)= | | 23x+5=25x-4 | | (x+5)/10=4/5+(x-5)/7 | | -[7x-(2x+2)]=-4-[3(3x-3)-2x] | | x(8-2)=11 | | 23x+5=25-4 | | (8-2)x=11 | | 9x+39=7x-2 | | 7(5y-6)+2(5y+4)= | | y=17.046x+19.242 | | 25-15*6+4=64 | | 13+35x=13 | | 7x+30=2x+100 | | S=3.14(h+k) | | 7x+65=2x+95 | | 5x+22=3x+56 | | -[6x-(2x+2)]=-5-[3(3x-4)-3x] | | p+1/2=-3/4p-1/8 | | y+5=-1/7(x-8) | | 8[p-1]=3[p+3] |

Equations solver categories